Sharing care : equal and primary carer fathers and early years parenting - Brooks, Rachel, 1971-; Hodkinson, Paul (Sociology of children and families series., 2020)
This timely study explores the experiences of fathers who take on equal or primary care responsibilities for young children. Offering academic insight and practical recommendations, this will be key reading for researchers, policymakers, practitioners and students interested in contemporary families.